2019
DOI: 10.3389/fncel.2019.00471
|View full text |Cite
|
Sign up to set email alerts
|

Dye Tracking Following Posterior Semicircular Canal or Round Window Membrane Injections Suggests a Role for the Cochlea Aqueduct in Modulating Distribution

Abstract: The inner ear houses the sensory epithelium responsible for vestibular and auditory function. The sensory epithelia are driven by pressure and vibration of the fluid filled structures in which they are embedded so that understanding the homeostatic mechanisms regulating fluid dynamics within these structures is critical to understanding function at the systems level. Additionally, there is a growing need for drug delivery to the inner ear for preventive and restorative treatments to the pathologies associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…This might increase the transduction rate while securing SGN survival. Approaches reported in the literature mostly aimed at administration to the perilymphatic space, combining, for example, round window injection with posterior semicircular canal fenestration (PSCC) or injection from the PSCC to the round window ( Yoshimura et al, 2018 ; Talaei et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might increase the transduction rate while securing SGN survival. Approaches reported in the literature mostly aimed at administration to the perilymphatic space, combining, for example, round window injection with posterior semicircular canal fenestration (PSCC) or injection from the PSCC to the round window ( Yoshimura et al, 2018 ; Talaei et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshimura et al described RWM injection with semicircular canal fenestration in PSCC as a safe technique for cochlear gene therapy (Yoshimura et al 2018). A study by Talaei et al reported that PSCC injection induces higher levels of dye delivery within neonatal and adult mice cochleae compared with RWM injections (Talaei et al 2019). Additionally, a technical shortcoming of PSCC injection is that it remains uncertain whether the injected therapeutic agent is administered into the endolymph or perilymph (Kawamoto et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The posterior semicircular approach (PSC) is used to access the vestibular organs, but is also capable of accessing the cochlea. A significant limitation of the PSC approach is the difficulty to determine whether the vector is injected into the endolymph or perilymph (Talaei et al, 2019 ). However, because of its relatively easy accessibility, the risk of surgical trauma and thus inner ear damage is decreased, which makes PSC an interesting delivery method (Isgrig and Chien, 2018 ; Ji et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%